TorPeDO: A Low Frequency Gravitational Force Sensor. (May 2016) - McManus, D. J.; Yap, M. J.; Ward, R. L.; Shaddock, D. A.; McClelland, D. E.; Slagmolen, B. J. J.
Abstract: Second generation gravitational wave detectors are likely to be limited by Newtonian Noise at low frequencies. A dual torsion pendulum sensor aimed at exploring low- frequency gravitational-force noise is being studied at the ANU. This sensor is designed to measure local gravitational forces to high precision and will be limited by Newtonian noise. We report on a controls prototype which has been constructed and suspended, along with initial characterisation and testing of the two torsion pendulums. Large weights at the end of each bar reposition the centres of mass to the same point in space external to both bars. Since both bars have a common suspension point, resonant frequency (≈33.4 mHz), and centre of mass, mechanical disturbances and other noise will affect both bars in the same manner, providing a large mechanical common mode rejection.